2018
DOI: 10.1017/jog.2018.43
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission signatures prior to snow failure

Abstract: Snow slab avalanches are caused by cracks forming and propagating in a weak snow layer below a cohesive slab. The gradual damage process leading to the formation of the initial failure within the weak layer (WL) is still not entirely understood. To this end, we designed a novel test apparatus that allows performing loading experiments with large snow samples (0.25 m2) including a WL at different loading rates and simultaneously monitoring the acoustic emissions (AE) response. By analyzing the AE generated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…It appears that load relaxation in combination with sintering changes the failure behavior from continuous to abrupt. These model results are in accordance to results of loading experiments of snow, where at high loading rates precursors to failure were observed, whereas for slow loading rates, for which sintering and load relaxation are supposed to be most relevant, no precursors were noted [9].…”
Section: B Load Relaxationsupporting
confidence: 89%
See 1 more Smart Citation
“…It appears that load relaxation in combination with sintering changes the failure behavior from continuous to abrupt. These model results are in accordance to results of loading experiments of snow, where at high loading rates precursors to failure were observed, whereas for slow loading rates, for which sintering and load relaxation are supposed to be most relevant, no precursors were noted [9].…”
Section: B Load Relaxationsupporting
confidence: 89%
“…For all strain rates, snow fails at strain and stress values that are much higher than the linear elastic limit [7]. This rate dependence of the failure behavior is also reflected in the acoustic emission (AE) response of snow (e.g., [8,9]). The AE response in turn is used for measuring precursors of material breakdown and to predict the time of failure.…”
Section: Introductionmentioning
confidence: 90%
“…In our case, the failure envelope is directly linked to ℎ , since any failure envelope can be expressed as a function of ℎ . Weak layer failure behavior was not affected by the heterogeneity induced by different types of random ball deposition and by the sample size if the sample size was larger than 0.3 m  0.3 m. This size is typically found in field tests (PST, ECT;van Herwijnen et al, 2016;Reuter et al, 2015;Bair et al, 2014) and laboratory experiments (Capelli et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…To select the model parameters and ℎ ,we used the elastic modulus computed as the derivative of the normal stressstrain curve and the strength values from the experiments (Table 1), as well as the relations for strength and modulus derived below. Digital image analysis of the experiments had revealed that the deformation was concentrated in the weak layer (Capelli et al, 2018). We therefore simulated the weak layer with a rigid actuator layer on the top.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Yet, it is known that the deformation of the weak layer is crucial for deformations and the local load transfer in the snowpack (Reiweger and Schweizer, 2010). Chiaia et al (2008) and Gaume et al (2013) consider weak-layer deformability only in shear.…”
Section: Introductionmentioning
confidence: 99%